Children's perceptions of learning with trainee teachers - Cooper, Hilary; Hyland, Rob (London : Routledge, 2000)
The big picture. Roles and responsibilities. Do pupils learn what trainee teachers teach? New faces, new ideas? Themes, dimensions and issues.
Keywords: Education; Great Britain; Children; Student teachers -- Great Britain -- Case studies; Education, Elementary -- Great Britain -- Case studies; Children -- Great Britain -- Attitudes -- Case studies